2014
DOI: 10.1186/1756-0500-7-820
|View full text |Cite
|
Sign up to set email alerts
|

Optimal doses of sevoflurane and propofol in rabbits

Abstract: BackgroundAlthough sevoflurane and propofol are commonly used anesthetics in rabbits, optimal doses of remain unclear. We thus assessed the optimal hypnotic doses of sevoflurane and propofol, and evaluated the influence of dexmedetomidine on sevoflurane and propofol requirements.MethodsTwenty-eight Japanese white rabbits were randomly assigned to one of four groups (n = 7 each). Rabbits were given either sevoflurane, propofol, sevoflurane + dexmedetomidine, or propofol + dexmedetomidine (injected 30 μg∙kg-1∙hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Regarding sevoflurane and DEX infusion in the present study, 5% sevoflurane was given to maintain the end-tidal sevoflurane at a maximum of 3.9%. 18,19 The 5% sevoflurane used in the present study was 2 to 3 times the minimum alveolar concentration of humans as is common for rabbits. For this reason, we set the infusion dose of DEX at 3 times that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sevoflurane and DEX infusion in the present study, 5% sevoflurane was given to maintain the end-tidal sevoflurane at a maximum of 3.9%. 18,19 The 5% sevoflurane used in the present study was 2 to 3 times the minimum alveolar concentration of humans as is common for rabbits. For this reason, we set the infusion dose of DEX at 3 times that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrated that rabbits require sevolurane ET concentrations of 3.9±0.2 to maintain unconsciousness in the absence of nociceptive stimulation. 11 The delivery of sevolurane and isolurane in the rabbits of the current investigation was titrated to efect at the discretion of the anaesthetist in charge, based on the results of the clinical monitoring of each patient. This resulted in sevolurane end-tidal concentrations that were slightly lower than those reported by Terada and colleagues, a inding that can be explained by the concomitant use of other anaesthetic and analgesic drugs that presumably decreased the minimum alveolar concentration of sevolurane.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study demonstrated that rabbits require sevoflurane ET concentrations of 3.9±0.2 to maintain unconsciousness in the absence of nociceptive stimulation 11 . The delivery of sevoflurane and isoflurane in the rabbits of the current investigation was titrated to effect at the discretion of the anaesthetist in charge, based on the results of the clinical monitoring of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary experiment and our previous study [ 11 ] showed that JM-1232(-) decreases BIS values. BIS is commonly used to measure hypnotic effect, and appears reliable in rabbits [ 12 ]. It therefore seems likely that JM-1232(-) decreased neural activity and CMR.…”
Section: Discussionmentioning
confidence: 99%